2010
DOI: 10.1016/j.ygcen.2010.02.002
|View full text |Cite
|
Sign up to set email alerts
|

17β-Estradiol levels in male zebra finch brain: Combining Palkovits punch and an ultrasensitive radioimmunoassay

Abstract: Local aromatization of testosterone into 17β-estradiol (E2) is often required for the physiological and behavioral actions of testosterone. In most vertebrates, aromatase is expressed in a few discrete brain regions. While many studies have measured brain aromatase mRNA or activity, very few studies have measured brain E2 levels, particularly in discrete brain regions, because of technical challenges. Here, we used the Palkovits punch technique to isolate 13 discrete brain nuclei from adult male zebra finches.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 63 publications
3
65
0
Order By: Relevance
“…E 2 was measured using an assay kit (#DSL-4800) from Beckman Coulter (inter-assay variation = 6.5%; intra-assay variation = 6.0%). Modifications to the instructions for the E 2 kit have been described elsewhere (27). Briefly, 100 ll of diluted primary antibody was added to 300 ll (150 ll of resuspended sample + 150 ll of PBSG) of standards and diluted samples and incubated for 4 h at room temperature.…”
Section: Radioimmunoassaysmentioning
confidence: 99%
“…E 2 was measured using an assay kit (#DSL-4800) from Beckman Coulter (inter-assay variation = 6.5%; intra-assay variation = 6.0%). Modifications to the instructions for the E 2 kit have been described elsewhere (27). Briefly, 100 ll of diluted primary antibody was added to 300 ll (150 ll of resuspended sample + 150 ll of PBSG) of standards and diluted samples and incubated for 4 h at room temperature.…”
Section: Radioimmunoassaysmentioning
confidence: 99%
“…While there are commercial kits available for testosterone, nothing is available for measuring estradiol in birds. Ironically, an extremely sensitive method for assaying 17-estradiol has recently been described, but this was developed to measure estrogens in the male brain [25], which are critical for the activation of male reproductive behaviors through the local aromatization of testosterone [9]. Another complication related to female physiology is that the rapid maturation of the ovarian follicles, mainly occurring during egg-yolk deposition, is sudden and transient and can easily be missed during sampling.…”
Section: Reducing the Sex-bias In Physiological Studiesmentioning
confidence: 99%
“…All of the genes required for de novo steroidogenesis are expressed in the zebra finch brain from as early as the first day of posthatch life (Jacobs et al, 1999;Kim et al, 2004;London et al, 2003London et al, , 2006London and Clayton, 2010;London and Schlinger, 2007;Shen et al, 1994Shen et al, , 1995. Biochemical enzyme assays demonstrated that all enzymes are present and active in the zebra finch brain and micropunches confirm generally that regional differences in steroid concentrations can be established (Cam and Schlinger, 1998;Charlier et al, 2010;Freking et al, 1998;Saldanha et al, 2000;Schlinger et al, 1994Schlinger et al, , 1995Schlinger and Arnold, 1991;Schlinger et al, 1999;Tam and Schlinger, 2007;Vanson et al, 1996;Wade et al, 1995). Further, the distribution of steroidogenic enzymes changes across the lifespan.…”
Section: Life Time: Spatial and Temporal Regulation Of Transcriptionmentioning
confidence: 64%